Molecular characterization of vancomycin-resistant enterococci isolated from a hospital in Beijing, China - Sun, Hong-Li; Liu, Chang; Zhang, Jing-Jia; Zhou, Yu-Ming; Xu, Ying-Chun (Journal of microbiology, immunology and infection, 2019)
To investigate the occurrence of vancomycin-resistant enterococci (VRE) isolated from patients in Peking Union Medical College Hospital, Beijing, China from 2011 to 2017, and to evaluate their resistance mechanisms and genetic relatedness. All isolates were identified using matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF). Antibiotic susceptibility testing was performed using the broth microdilution method. Molecular characterization were detected by PCR and sequencing. Genotyping of VRE isolates was performed by multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE) analysis. Virulence genes were detected by multiplex PCR. A total of 87 consecutive VRE were collected, including 84 isolates of vancomycin resistant Enterococcus faecium (VREfm) and 3 isolates of Enterococcus faecalis (VREfs). Urine (40.2%, 35/87) and blood (17.2%, 15/87) were the most commonly specimens. All VREfm isolates were resistant to ampicillin, and were susceptible to daptomycin, linezolid and tigecycline. The resistant rate of teicoplanin was 47.6%. All of the VREfm isolates carried the vanA gene, no isolates carried vanB. 11.9% (10/84) VREfm isolates carried both vanA and vanM. Among them, 76.2% (64/84) and 66.7% (56/84) carried esp and hyl, respectively. The 3 vancomycin resistant E. faecalis (VREfs) isolates were varied, and only one carried vanB. A total of 3 and 18 STs were detected among VREfs and VREfm strains, respectively. PFGE results indicated a genetic diversity among VREfm isolates. This study confirms that VREfm isolates associated with ST78 were the main epidemic lineage responsible for nosocomial infections in China, as were also observed in other nations worldwide.